PUPIL PROJECT AND ACTIONS IN HEALTH: PERSPECTIVE OF YOUNG PEOPLE ENTERING IN THE JOB MARKET (Fiep Bulletin - online, 2011)
Introduction: Due to the difficulty that young people face to get in the labor market, mainly who are socially vulnerable, the initiative of Pioneer Sementes company, through Pupil Project, shows its social responsibility and contribution for the society. It is developed in partnership with the University of Santa Cruz do Sul (UNISC) and the catering company Prato Feito, aiming the youths' training for entering the labor market, including health care. Objective: This study's objective was to identify the project participants' health profile, regarding to physical fitness. Methodology: Twenty teenagers were evaluated, ranging from 16 to 19 years old. The data collected were: body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), flexibility test (cuff and sit and reach tests), abdominal test (AbT) and push-up, and Rockport mile test. Results: In  BMI, 20% of the subjects were classified as "overweight"; 25% " from below the average to poor", in the % G; and 25%   out "increased" cardiovascular risk, in WC; and 30% "high risk" and "very high risk", in WHR; more evidenced in the feminine sex. In the dynamic muscular resistance 50% of the subjects obtained "poor" classification, in AbT, and 45% "average" in press-up test; in the flexibility, 45% and 40% were "below the average to the low condition", in right cuff and sit and reach tests, respectively. In the cardio respiratory aptitude 65% of the subjects were classified as "good", 10% indicated presence of light hypertension. Conclusion: We observed good cardio respiratory physical condition; however, considering their age group, the indexes of weight excess and central fat distribution were little healthy, like the muscle-skeletal health. It indicates the necessity to rethink those teenagers' lifestyle, aiming an improvement in their life quality.
Keywords: job market; lifestyle; actions in health